Genetic and biochemical evidence for a functional role of BACE1 in the regulation of insulin mRNA expression. (5th July 2013) - Hoffmeister, Albrecht; Tuennemann, Jan; Sommerer, Ines; Mössner, Joachim; Rittger, Andrea; Schleinitz, Dorit; Kratzsch, Jürgen; Rosendahl, Jonas; Klöting, Nora; Stahl, Tobias; Roßner, Steffen; Paroni, Federico; et al.
<x xml:space="preserve">Abstract</x> Objective Beta‐site amyloid precursor protein cleaving enzyme (BACE1) is highly expressed in pancreatic β‐cells. The BACE1 gene is located in a region associated with a high diabetes risk in PIMA Indians. Design and Methods INS‐1E cells were used to study the impact of siRNA‐mediated BACE1 knockdown and glucose metabolism was characterized in Bace1–/– mice. BACE1 gene was sequenced in DNA samples from 48 subjects and 13 representative single nucleotide polymorphisms (SNPs) were then genotyped for association studies in 1, 527 Caucasians. Results Reduction of Bace1 expression results in a significant decrease in insulin mRNA expression in INS‐1E cells. Bace1–/– mice display significantly lower body weight, lower plasma insulin concentrations, but normal glucose tolerance and insulin sensitivity. In a case‐control study including 538 healthy controls and 989 patients with type 2 diabetes (T2D), one SNP (rs535860) was significantly associated with T2D (P < 3.5 × 10−5, adjusted for age, sex, and BMI). Conclusions Reduced Bace1 expression causes impaired insulin expression in pancreatic β‐cells of Bace1–/– mice, suggesting that BACE1 plays a role in the regulation of insulin biogenesis. The functionally relevant rs535860 SNP may decrease BACE1 expression by creating a new miR‐661 binding site and could therefore contribute to T2D development.